Concurrent prenatal drinking and smoking increases risk for SIDS: Safe Passage Study report. (February 2020) - Elliott, Amy J.; Kinney, Hannah C.; Haynes, Robin L.; Dempers, Johan D.; Wright, Colleen; Fifer, William P.; Angal, Jyoti; Boyd, Theonia K.; Burd, Larry; Burger, Elsie; Folkerth, Rebecca D.; Groenewald, Coen; et al.
Abstract: Background: Sudden infant death syndrome (SIDS) is the leading cause of postneonatal mortality. Although the rate has plateaued, any unexpected death of an infant is a family tragedy thus finding causes and contributors to risk remains a major public health concern. The primary objective of this investigation was to determine patterns of drinking and smoking during pregnancy that increase risk of SIDS. Methods: The Safe Passage Study was a prospective, multi-center, observational study with 10, 088 women, 11, 892 pregnancies, and 12, 029 fetuses, followed to 1-year post delivery. Subjects were from two sites in Cape Town, South Africa and five United States sites, including two American Indian Reservations. Group-based trajectory modeling was utilized to categorize patterns of drinking and smoking exposure during pregnancy. Findings: One-year outcome was ascertained in 94·2% infants, with 28 SIDS (2·43/1000) and 38 known causes of death (3·30/1000). The increase in relative risk for SIDS, adjusted for key demographic and clinical characteristics, was 11·79 (98·3% CI: 2·59–53·7, p < 0·001) in infants whose mothers reported both prenatal drinking and smoking beyond the first trimester, 3.95 (98·3% CI: 0·44–35·83, p = 0·14), for drinking only beyond the first trimester and 4·86 (95% CI: 0·97–24·27, p = 0·02) for smoking only beyond the first trimester as compared to those unexposed or reported quitting early in pregnancy. Interpretation: Infants prenatally exposed to both alcohol and cigarettes continuing beyond the first trimester have a substantially higher risk for SIDS compared to those unexposed, exposed to alcohol or cigarettes alone, or when mother reported quitting early in pregnancy. Given that prenatal drinking and smoking are modifiable risk factors, these results address a major global public health problem. Funding: National Institute on Alcohol Abuse and Alcoholism, Eunice Kennedy Shriver National Institute of Child Health and Human Development, and the National Institute on Deafness and Other Communication Disorders.